"Interior view of a hut ...": Stereography and the depiction of an Interior Architecture in 1930 - Wood, Peter; Dudding, Michael (Architectural History Aotearoa, 2021)
This paper is an exploration of a stereographic photograph taken inside a New Zealand backcountry hut. Matter-of-factly entitled, "Interior view of a hut, with mugs, a bottle, plate and cutlery on a table, looking through door to another hut, location unidentified," the photograph is attributed by the Alexander Turnbull Library to keen amateur photographer Edgar Richard Williams. The image gives little detail away in its depiction of the hut interior, except for a utilitarian table tableau that begins to suggest a nascent New Zealand interior defined by no-nonsense pragmaticism and Lea & Perrins. But, far from being a scene of Depression-era poverty and deprivation, close examination of the photographed situation and its broader context provides a glimpse into a monied amateurism that heralded an emergent leisure class. As a stereoscopic image, the photograph does more than depict a scene. By placing us within a spatial view, we become immersed in questions concerning interiority and exteriority. We are presented with two spatial contrasts: one in the subject of the image, the other in the object of the image. By taking a close reading of both contrasts, this paper is an attempt to make some architectural sense of these dualities.